Implementasi Teks Mining Untuk Klasifikasi Buku Berdasarkan Dewey Decimal Clasification (Ddc) Di Perpustakaan Stmik Asia Malang Berbasis Vektor Space Model - Jatmika, Sunu; Indriastuti, Maria Theresia; Wafdulloh, Gibran Adna (P3M Politeknik Negeri Banjarmasin, 2018)
ASIA University Library has a problem in the grouping of new books in large numbers, because the DDC is a parameter for the grouping of the book has not been entered into the library information system, so that when the librarian input some books, they should be viewed DDC before entering into the system and it was very reducing the work time efficiently. Those problems can be solved by adding the new intelligent system in the application, namely the pre-processing algorithms that has tokenizing phase, filtering, and stemming use Nazief Andriani and then compared to find similarities documents or title with Vector Space Model algorithm. From the test that results using the algorithm above, eventually the system could resolve the problems in the library of ASIA that is this system has a recall value by 63% and the value of Precision by 72%. These results meet on the effectiveness of information retrieval system that the accuracy of a value is at least 50%.